Barriers of Continuous Glucose Monitor Use in Patients with Type 1 DM in Tabuk Region, KSA 2025 - Alharbi, Asma Ali; Albalawi, Ahmad Raja Saeed; Alharbi, Amal Ali; Alfaer, Sarah Abdulleh; Alanizi, Areej Daham (Journal of Neonatal Surgery, 2025)
Background: CGM devices, commonly known as self-monitoring devices, are essential in diabetes management since they offer real-time glucose level information. This research proposes determining the level of awareness, usage, level of satisfaction with the CGM devices and perceived barriers among the adult Type 1 diabetes patients. Awareness of these factors should facilitate further use of CGM devices and enhance the outcomes of diabetes treatment. Method: Closed-ended questions were used in order to administer a structured questionnaire among participants with type 1 diabetes. Demographics, Diabetes self-management activities, awareness about CGM devices, ever use, level of satisfaction and perceived barriers were captured in the self-administered questionnaire. Participants also assigned scores for their perception of CGM capabilities and gave some details about the preferable functionality of the system and the maximum allowable project cost. To this end, data was analyzed descriptively with a view of establishing trends and significant patterns in the use and perceived importance of CGMs. Result: The respondents were randomly selected across the age, education and employment status spectrum. A considerable number of participants, 90.7 % admitted to having seen or known CGM devices, but only 70.1 % had ever used them. Finding: For the 74.6 % of the users are also found to be either satisfied or very satisfied with the device. The survey revealed that cost was the foremost reason why more than half of the non-users were unable to incorporate WP. Some of the participants said they were willing to pay less than 100 SAR per month for CGM devices. Perceived usefulness defined as accuracy, ease of use of a monitor and continuous data monitoring for decisions were seen as crucial. In addition, as many as 80% of respondents claimed that CGM use might enhance diabetes control. Conclusion: According to this study’s findings out of those who are aware that CGM devices exist, their utilization is limited mainly by cost factors. In general, there were quite favorable assessments of the devices, pointing out that such aspects as accuracy and convenience are crucial. The financial barriers should be eliminated by the provision of subsidies for the devices or affordable models of the technology would greatly increase the use and benefit of the CGM technologies for Diabetes Management. Future research, therefore, must cover how to make CGM devices more accessible and how to make people understand that they should use the devices in the first place. It is suggested that more studies should be conducted in order to empirically test more specific strategies for addressing difficulties and increasing the utilization of CGM technology.